PENEGAKAN HUKUM DALAM PERADILAN TATA USAHA NEGARA DI INDONESIA - TRILASSIWI, WORO (Wacana Hukum, 2009)
Abstract: there are four factors influencing the law enforcement especially state administrative justice. They are the law (UU No 5 1986 jo UU No 9 2004), the law enforcers, the infrastructure and the society.  If they all work well, the law enforcement in state administrative justice will also work well. Keywords: law enforcement, state administrative justice